Evaluation of the profile of drug therapy administered through enteral feeding tube in a general hospital in Rio de Janeiro - Mario Jorge Sobreira da Silva; Carlos Eduardo Meireles Cava; Patrícia Kaiser Pedroso; Débora Omena Futuro (Universidade de São Paulo, 2011)
Enteral nutrition (EN) is the method of choice for patients that cannot adequately receive oral feeding despite good gastrointestinal tract condition. Enteral diets may be administered through tube or ostomy placed in the stomach, duodenum or jejunum. The administration of drugs via enteral feeding tube (EFT) is a common practice in hospitals due to patient clinical status, and requires special attention from professionals involved in this process. This study entailed an analysis of the profile of drug therapy through EFT based on evaluation of medical prescriptions of the Medical Clinic of the Hospital dos Servidores do Estado (HSE) of Rio de Janeiro sent to the Pharmacy Service between January and June 2007, according to standard protocols in place. Prescription of drugs via EFT outside recommended guidelines was observed, besides potential drug-nutrient incompatibilities associated with this practice. These results point to the need for improvement of enteral route access and the adoption of measures to promote safe and effective use of drugs and nutritional therapy. A nutrição enteral (NE) é o método de escolha para alimentar pacientes que não podem receber alimentação por via oral de forma adequada, mas que estejam com a função gastrointestinal satisfatória para a absorção dos nutrientes. As dietas enterais podem ser administradas através de cateteres ou ostomias, posicionados no estômago, duodeno ou jejuno. A administração de medicamentos através de cateter de nutrição enteral (CNE) é uma prática muito comum no ambiente hospitalar, devido ao estado clínico do paciente, necessitando atenção especial dos profissionais envolvidos neste processo. O estudo constituiu uma análise do perfil da terapia medicamentosa através de CNE por meio de uma avaliação das prescrições médicas da Clínica Médica do Hospital dos Servidores do Estado (HSE) do Rio de Janeiro encaminhadas ao Serviço de Farmácia, de janeiro a junho de 2007, tendo como padrão protocolos existentes. Foi observada a prescrição de medicamentos através do CNE fora das recomendações contidas nas referências, além de possíveis incompatibilidades fármaco-nutriente associadas a esta prática. Os resultados demonstraram a necessidade de melhoria na utilização dessa via e adoção de medidas a fim de promover um uso seguro e eficaz de medicamentos e da terapia nutricional.